Effects of a myostatin mutation in Japanese quail (Coturnix japonica) on the physicochemical and histochemical characteristics of the pectoralis major muscle - Kim, Dong-Hwan; Lee, Boin; Lee, Joonbum; Bohrer, Benjamin M.; Choi, Young Min; Lee, Kichoon (Frontiers in Physiology, 2023)
This study was to compare the carcass, meat quality, and histochemical characteristics of pectoralis major (PM) muscle between wild type (WT) and myostatin (Mstn) homozygous mutant (HO) quail lines. The HO quail line exhibited significantly heavier body (approximately 10%) and PM muscle (approximately 20%) weights compared to the WT (p < 0.001). However, the two groups had similar traits for meat quality, although slightly higher lightness and cooking loss were observed in the mutant quail (p < 0.05). For histochemical traits of PM muscle, Mstn mutant quail exhibited lower type IIA and higher type IIB percentage in the deep region than WT quail (p < 0.05), indicating a fiber conversion from the type IIA to IIB. Whereas, the two quail lines had comparable histochemical traits in the superficial region (p > 0.05). These findings provided that Mstn can be a candidate gene for increasing meat production without affecting meat quality in the poultry species.